Pre-Islamic Poet Between The Arbitrariness Of Social Traditions And Psychological Mechanisms Of Defense - منعم, مشتاق طالب; حسوني, شيماء زاحم (Al-Adab Journal, 2019)
In the middle of desert environment that far parties disassociated their citizens from welfare means and it also distanced them to achieve prosperity and well-off, as well as establishing psychological and social balance. Thus, it is the community which can be termed as a heterogeneous mixture, who created its laws with more similarity to its formative structure. Taking the law ((survival for the strongest)) means to enact such laws, therefore, various problematic are done, one of those problems for instance was the phenomenon of tribal arbitrariness. A tribe represents with its special system the active focus and legitimate and formal cover that constrained the self-poet as well as limiting his/her movement perfectly. That cover was so represented mores and social traditions that have dominated the will of everyone, and this justified the existence of patterns of self-regulation was far away from the principle of democracy, and falls under those patterns all examples of racism, discrimination and the self, as well as took off those laws sometimes secretly has resorted to the declaration and come up and the revolution and sometimes trying to break down the restrictions.This research is a serious attempt to find out ways, means and mechanisms that a poet, who represents media tongue, tried by them go out and revolution on the social norms and traditions mutinously at times, and to be fugitive at the other. And he was practicing other ways to compensate or salvation, forcing him presumably. Meanwhile, we do not forget that the poet sometimes succumbs to the will of the stronger as a result of environmental conditions which imposed by nature, as well as that there are a lot of acts can not be based on the individual, so he found himself imposed to integrate with tribalism and keep pace with the group.The research stands on three axes, the first devoted to clarify the terminologies that contained in the title, then the second axis allocated to the study of the pre-Islamic society components , and the factors that contributed actively in the formation of the structure of that society to enact laws, while the third axis studied the defense mechanisms working, which appeared images of various Pre-Islamic poets, some of them took compensation, while the others took recidivism, inhibition, daydream, reverse formation, etc., in order to achieve a psychological balance. And we show the psychological impact that they had experienced in their community who stood a barrier to achieving many of the desires that individuals aspire. It should be noted that the poets, in this study, reflect different classes of that society, because we find that their poetry increasing the accuracy of the results and the assumptions that we have reached.Sealing this research with a conclusion that included the most important of our findings.